PAS: A new powerful and simple quantum computing simulator. (29th October 2021) - Bian, Haodong; Huang, Jianqiang; Tang, Jiahao; Dong, Runting; Wu, Li; Wang, Xiaoying
Abstract: In recent years, many researchers have been using CPU for quantum computing simulation. However, in reality, the simulation efficiency of the large‐scale simulator is low on a single node. Therefore, striving to improve the simulator efficiency on a single node has become a serious challenge that many researchers need to solve. After many experiments, we found that much computational redundancy and frequent memory access are important factors that hinder the efficient operation of the CPU. This paper proposes a new powerful and simple quantum computing simulator: PAS (power and simple). Compared with existing simulators, PAS introduces four novel optimization methods: efficient hybrid vectorization, fast bitwise operation, memory access filtering, and quantum tracking. In the experiment, we tested the QFT (quantum Fourier transform) and RQC (random quantum circuits) of 21 to 30 qubits and selected the state‐of‐the‐art simulator QuEST (quantum exact simulation toolkit) as the benchmark. After experiments, we have concluded that PAS compared with QuEST can achieve a mean speedup of 8 . 69 × (QFT), 2 . 62 × (RQC) (up to 10 . 76 ×, 4 . 87 × ) on the Intel Xeon E5‐2670 v3 CPU.